Management Strategies of Ocular Alkaline Chemical Injury: Poster Presentation - Case Report - Resident - Nadia Ayu Destianti; Patrioka Muslima; Elfa Ali Idrus; Arief Akhdestira; Angga Fajriansyah (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ocular chemical burns are true ophthalmic emergencies that can cause permanent corneal and intraocular damage leading to visual impairment or even blindness. When a case of chemical trauma occurs, immediate and appropriate management should be done. Case Illustration : A 24-year-old man came to Cicendo Eye Hospital with complaints of blurry eyes accompanied by burning and watery eyes after being doused with a bucket of cement mortar two weeks earlier. Ophthalmologic examination obtained visual acuity for the right eye 1/300 and left eye was 1/60. The anterior segment of both eyes showed corneal edema, conjunctivalization, persistent epithelial defects, limbal ischemia, and punctate epithelial erosion. There was an ulcer and thinning of the corneal layer in left eye. He was diagnosed with alkaline chemical injury Dua's classification grade VI on the right eye and grade V on the left eye (Figure 1). The patient then underwent a keratectomy, conjunctival resection, and amniotic membrane transplantation procedure. On the seventh day postoperatively, symptoms and clinical features improved with the visual acuity of both eyes improved to 1/60 (Figure 2). Discussion : Amniotic membrane graft was performed in late reparative phase which aims to preserve the surface of the corneal epithelium and prevent corneal perforation and inflammation. Conjunctival resection was performed to prevent neovascularization of the amniotic membrane. Conclusion : Management of ocular burn injury requires an immediate and comprehensive treatment to achieve good result. In this case successful treatment was achieved by improvement of visual acuity and no complication occured.